2020
DOI: 10.5688/ajpe7489
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pharmacy Students’ Metacognition Through Self-Evaluation During Advanced Pharmacy Practice Experiences

Abstract: Objective. To explore whether metacognition can be improved in Doctor of Pharmacy (PharmD) students through routine self-assessment over a year-long advanced pharmacy practice experience (APPE) sequence. Methods. Differences between self-assessment scores and preceptors' scores for three cohorts of pharmacy students between 2015 and 2018 were compared between the first, second, and third trimester to determine whether students more accurately evaluated their performance over time. The primary endpoint was chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…So far, pharmaceutical educators have employed some teaching strategies for the improvement of students' metacognition. [16][17][18][19][20][21][22][23] In a review conducted by Medina et al 16 interventions including exam reviews, cognitive apprenticeships, thinking out loud protocols, modeling of personality and has been well-accepted among personality psychologists. [5][6][7]9 Here, we reported a strong positive correlation between overall MCQ-30 scores and NEO-FFI conscientiousness among pharmacy students, which was evaluated using Pearson correlation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, pharmaceutical educators have employed some teaching strategies for the improvement of students' metacognition. [16][17][18][19][20][21][22][23] In a review conducted by Medina et al 16 interventions including exam reviews, cognitive apprenticeships, thinking out loud protocols, modeling of personality and has been well-accepted among personality psychologists. [5][6][7]9 Here, we reported a strong positive correlation between overall MCQ-30 scores and NEO-FFI conscientiousness among pharmacy students, which was evaluated using Pearson correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the ever-changing nature of the pharmacy profession, which requires ongoing selfassessment of knowledge and skills as well as life-long learning, the importance of metacognition skill training in pharmaceutical education has been highlighted in recent years. [16][17][18][19][20][21][22][23] During the learning process, pharmacy students need metacognitive skills to supervise and adjust their thinking, understanding and reasoning and problem-solving, that are underlying components or desired outcomes of pharmaceutical curricula. Metacognition is essentially a means to address "what" "when" and "how" to learn.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have reported overconfidence of students and no improvement of self-assessment accuracy [11][12][13] but results from another study showed improvement in self-awareness over three semesters. 14 After the introduction of "benchmark performance" (defined in this context as a self-assessment of performance compared with an expert response), self-ratings became more aligned with expert's ratings. 13 Due to the different approaches employed in the literature, self-assessment accuracy warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%